2016
DOI: 10.26555/jpsd.v2i2.a5485
|View full text |Cite
|
Sign up to set email alerts
|

Penguatan Literasi Informasi Berbasis Perpustakaan Bagi Peningkatan Mutu Akademik Mahasiswa Pgmi Iain Cirebon

Abstract: This study aims to determine: 1) How Information Literacy Strengthening Program for students in primary IAIN Cirebon. 2) Strengthening Program Implementation Based Information Literacy Libraries For students in primary IAIN Cirebon. 3) Strengthening the Effectiveness of Information Literacy Library Based on Academic Quality Improvement in primary students IAIN Cirebon.This research is classroom action research. The stages in the cycle of action research are: Planning, Implementation of the action, Observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This shows that digital literacy in education is still very lacking because the information is widespread in existing social networks. In order to realize independent learning, educators need to improve literacy as a prerequisite for 21st century life skills (Syamsi, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This shows that digital literacy in education is still very lacking because the information is widespread in existing social networks. In order to realize independent learning, educators need to improve literacy as a prerequisite for 21st century life skills (Syamsi, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…So that the ability of information literacy in the media becomes a relevant need to be immediately carried out to develop the empowerment of netizens in responding to the spread of hate messages in the online realm, especially through social media [17]. Other research also found that there was an effective increase in the academic scores of students after they were given an information literacy strengthening program [18].…”
Section: Basic Ontology Information Literacymentioning
confidence: 99%
“…Low information literacy has triggered the spread of fake news [3], [4], thus having an information literacy skill becomes a need in order to develop one's ability, especially as a netizen, to deal with the spread of hate messages in the online domain, especially through social media [5]. Other studies also found that there was an effective increase in students' academic grades after they were given information literacy strengthening programs [6]. Teaching information literacy equips students with an anti-plagiarism attitude and encourages personal formation as an independent learner and prepares them to be a producer of information or knowledge based on ethics and scientific rules [7].…”
Section: Introductionmentioning
confidence: 99%